Knowledge Sharing is The Key Success Factor to Building Competitive Advantage in Indonesia: a Review and Hint for Future Research - Sarah Sentika; Rivaldi Arissaputra (Budapest International Research and Critics University, 2022)
Today's development of information and technology requires companies to focus on managing knowledge management, Knowledge Sharing. This is one of the drivers in the company's progress to can compete. This study aims to review and integrate the literature from several previous studies regarding Knowledge Sharing, which examines the implications of implementing knowledge sharing for companies and what things encourage people to share knowledge in Indonesia. This study conducted a narrative review of the literature using the Systematic Literature Review (SLR) method in Scopus indexed journals. 121 articles were selected with four filtering stages to produce 20 articles. The results of the study are: Knowledge Sharing can be applied in different fields; Research on Knowledge Sharing is subjective due to differences in work values and interactions with technology from time to time; Factors that influence Knowledge Sharing include motivation, learning, sharing opportunities, relationships, communication, trust, satisfaction, environmental culture, nature of knowledge, hard rewards, a pleasure to help others, soft rewards, and self-efficiency; and Knowledge Sharing can have a positive impact on the company.